P-099 PERSISTENT POST-SURGICAL PAIN AFTER SURGICAL CORRECTION OF VENTRAL HERNIA REPAIR. PRELIMINARY DATA OF AN OBSERVATIONAL STUDY AT VARESE UNIVERSITY HOSPITAL. (13th October 2022) - Novazzi, C; Guzzetti, L; Selmo, G; D'onofrio, D F; Latham, L; Gianazza, S; Cannavo', M; Cabrini, L; Pappalardo, V; Bacuzzi, A; Inversini, D; Ietto, G; et al.
Abstract: Aim: Persistent post-surgical pain (PPSP) is one of the most frequent complication after surgery and has important socio-economic consequences. Materials and methods: We performed an observational analysis of the patients submitted to surgical correction of ventral hernia repair at our University Hospital between 1st February 2021 and 1st January 2022.We registered data about perioperative surgical period. After at least 3 months we proceeded with a phone interview in order to record the incidence of PPSP according to its definition. Results: We enrolled 61 patients and 26 patients were lost to follow-up. 9 patients (25%) denveloped chronic pain after surgery and 3 cases reported pain that had deteriorated the quality of life (PPSP group).In the PPSP group median age was 53; obesity, COPD, diabetes mellitus, smoking status, were not significant (p > 0, 05). Male sex, previous abdominal surgery and open approach showed correlation with PPSP onset. In our cohort demographical and clinical characteristics were not statistically related to PPSP, while the use of locoregional anesthesia could be protective in front of PPSP onset. Conclusion: At the moment, although there is no shared protocol in the prevention of PPSP, it is possible to implement some interventions to reduce its risk. Our results show that more effective analgesic/anesthetic perioperative measures may help to prevent the adverse consequences of poorly controlled pain, including its transition to PPSP. The main limits of our data is the small cohort analysed and the study protocol without an analysis about immediate postoperative pain and PPSP outbreak.